Design of an Energy-Efficient and Environmentally Friendly Tourist Vessel to Address Tourism Strategy Challenges in the Riau Islands Province - Muhd Ridho Baihaque; Weldy Anugra Riawan; Deny Nusyirwan; Adyk Marga Raharja; Anton Hekso Yunianto; Firman Apriansyah (WAVE: Jurnal Ilmiah Teknologi Maritim, 2026)
Riau Islands Province as a maritime region is known for its marine tourism and tourist attraction on small islands. Answering the current challenges in tourism sector of Riau Islands Province is through the support of reliable and eco-friendly infrastructure to support attractiveness of marine tourism especially in terms of tourism ship design. The aim of this research is to design energy efficiency tourism ship by applying renewable energy using solar panels that can reduce exhaust emission and energy efficiency. Innovation of energy saving tourism ship was designed by analyzing the maximum GZ stability at 2,603 m at 67.3 degrees at the ship's maximum draft. By utilizing bottom glass platform technology that can directly see underwater coral reefs, this tourism ship has become a ship with the latest innovations with the application of renewable energy technology that answers the challenges of tourism strategies in the Riau Islands Province region.